Crosstalk between high-density lipoproteins and endothelial cells in health and disease: Insights into sex-dependent modulation - Dietrich, Elisa; Jomard, Anne; Osto, Elena (Frontiers in Cardiovascular Medicine, 2022)
Atherosclerotic cardiovascular disease is the leading cause of death worldwide. Intense research in vascular biology has advanced our knowledge of molecular mechanisms of its onset and progression until complications; however, several aspects of the patho-physiology of atherosclerosis remain to be further elucidated. Endothelial cell homeostasis is fundamental to prevent atherosclerosis as the appearance of endothelial cell dysfunction is considered the first pro-atherosclerotic vascular modification. Physiologically, high density lipoproteins (HDLs) exert protective actions for vessels and in particular for ECs. Indeed, HDLs promote endothelial-dependent vasorelaxation, contribute to the regulation of vascular lipid metabolism, and have immune-modulatory, anti-inflammatory and anti-oxidative properties. Sex- and gender-dependent differences are increasingly recognized as important, although not fully elucidated, factors in cardiovascular health and disease patho-physiology. In this review, we highlight the importance of sex hormones and sex-specific gene expression in the regulation of HDL and EC cross-talk and their contribution to cardiovascular disease.